PERBEDAAN PENURUNAN TEKANAN DARAH PASIEN HIPERTENSI YANG DIBERIKAN TERAPI AMLODIPIN PADA PAGI HARI DAN MALAM HARI DI PUSKESMAS BAYANAN KABUPATEN HULU SUNGAI SELATAN - Khalisah; Nurul Mardiati; Lisa Setia; Saidillah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Research of amlodipine drug therapy time against a decrease in blood pressure showed different results, it had a significant and insignificant effect. Research aimed to identify differences blood pressure reduction hypertension patients who give amlodipine drug therapy in the morning with night at the Puskesmas Bayanan Hulu Sungai Selatan Regency. This research method is obsevasional descriptive with Pre and post test design. There are two groups in this design, namely hypertension patients who give amlodipine drug therapy in the morning and night, blood pressure measured before and after 10 days observation, then compared between the difference in the decrease blood pressure of patients given amlodipine drug therapy in the morning and night. Results of respondents who give amlodipine drug therapy in the morning experienced average decrease in blood for systole -13.67 mmHg and diastole -6.33 mmHg. Amlodipine therapy at night experienced an average decrease in blood for cystole -19 mmHg and diastole -10.33 mmHg. Wilcoxon sigh test results for pressure systole values Asymp.sig. 0.007 and diastole pressure values Asymp.sig. 0.003 or <0.05 which states hypothesis is accepted, or there is a difference between a decrease blood pressure of hypertension patients give amlodipine drug therapy in the morning and night.